Internal factors affecting the performance of small and medium enterprises in Kosovo - Loku, Afrim; Nadire Loku (Technium Social Sciences Journal, 2020)
This study aims to provide an understanding of the importance of the SME sector in the socio-economic development of Kosovo and examine in particular the influence of internal factors on them. A cross-sectional survey was conducted with Kosovo SMEs through an anonymous online questionnaire. This study confirms that all internal factors - managerial skills and competencies, business experience, access to finance and technological capabilities, depending on a period, have a significant impact on the performance of SMEs. While access to finance is considered as a major challenge, technology is considered to help improve business performance. However, results revealed that poor managerial skills and competencies, despite having a significant impact on the performance of SMEs, they were also related to access in finance and technological skills, making it difficult to run a business. Training and empowerment of SME managers in key business areas can be an opportunity to improve business performance.